Optimal Control of a Delay-Varying Computer Virus Propagation Model - Jianguo Ren; Yonghong Xu; Chunming Zhang (Discrete Dynamics in Nature and Society)
By incorporating the objective of keeping a low number of infected nodes and a high number of recovered nodes at a lower cost into a known computer virus model (the delay-varying SIRC model) extended by introducing quarantine, a novel model is described by means of the optimal control strategy and theoretically analyzed. Through the comparison of simulation results, it is shown that the propagation of computer virus with varying latency period can be suppressed effectively by the optimal control strategy.